Design, synthesis and evaluation of benzodioxole and bromofuran tethered 1,2,4-triazole hybrids as potential anti breast cancer agents with computational insights - Manjunath R; Sushruta S. Hakkimane; Shashikala B S; Santhosh L. Gaonkar (Scientific Reports)
Abstract 1,2,4-Triazole derivatives are the focus of extensive research in medicinal chemistry because of their diverse biological activities, particularly their potential as anticancer agents. In this study, we designed and synthesized six compounds featuring benzo[d][1,3]dioxole and 5-bromofuran tethered to 1,2,4-triazole hybrids. This was achieved through an efficient four-step protocol with reproducible results. The characterization of the 1,2,4-triazoles was conducted via various analytical techniques, including FTIR, 1H NMR, 13C NMR, and mass spectrometry. The in vitro anti-breast cancer activities of synthesized 1,2,4-triazols were evaluated against the MCF-7 cell line using the MTT assay. Among all the synthesized compounds, compound 12b demonstrated an excellent IC50 value of 3.54 ± 0.265 µg/mL. Additionally, in silico studies, such as molecular docking to predict the orientation of the compounds, molecular dynamics simulations to evaluate binding stability with the target protein, drug-likeness studies to evaluate Lipinski’s rule of five and Jorgensen’s rule of three, DFT analysis to determine the energy gap of the frontier molecular orbitals (FMOs) and the molecular electrostatic potential (MEP) for identifying sites of nucleophilic and electrophilic attacks, were also conducted.